2013
DOI: 10.1063/1.4852675
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the mechanical behavior of alloys on their electron work function—An alternative parameter for materials design

Abstract: Mechanical and thermal behaviors of nitrogen-doped Zr-Cu-Al-Ag-Ta--An alternative class of thin film metallic glass Appl.In this article, we demonstrate that the electron work function (EWF) as an intrinsic parameter can provide information or clues in a simple or straightforward way for material design, modification, and development. A higher work function of a material represents a more stable electronic state, which consequently generates a higher resistance to any attempt of changing the electronic state a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 23 publications
(24 reference statements)
3
24
1
Order By: Relevance
“…It has been demonstrated that the mechanical behaviors (including bulk modulus, Young's modulus, hardness, and yield stress) of metals can be characterized by their electron distributions. 34,54,59,[62][63][64] As shown in, our predicted EWF of Mg agrees well with previous experimental 52 and theoretical data. 65 By selecting different reference states, the variations of EWF (Du 1 and Du 2 ) are defined as:…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It has been demonstrated that the mechanical behaviors (including bulk modulus, Young's modulus, hardness, and yield stress) of metals can be characterized by their electron distributions. 34,54,59,[62][63][64] As shown in, our predicted EWF of Mg agrees well with previous experimental 52 and theoretical data. 65 By selecting different reference states, the variations of EWF (Du 1 and Du 2 ) are defined as:…”
Section: Resultssupporting
confidence: 93%
“…As mentioned previously, many efforts have been made to correlate the concentration of solute atoms to the variation of hardness in Mg alloys, 24,34,35 and the hardness of metal materials has been correlated with EWFs. 54,64 In the next section, the EWF and hardness of Mg-Gd-based alloys will be discussed. EWF and Hardness of Mg-Gd/Y-Zn-Zr-Ag Alloys Figure 6 shows the effect of solute atoms on the age-hardening behavior and the EWF-dependent hardness of Mg-Gd-TM (TM = Ag, Zn, and Zr) alloys.…”
Section: Resultsmentioning
confidence: 99%
“…5(a) -schematic illustration). In this case, the material having a higher EWF should have a larger adhesive force, since the atomic bond energy is proportional to ϕ 6 [17][18][19] and a larger atomic bond energy results in a higher surface energy (for surfaces having the same broken-bond density) [1,15,20]. The EWFs of both stainless steel samples are higher than that of Ti1, thus their larger frictional coefficients are expected.…”
Section: Resultsmentioning
confidence: 94%
“…The EWF represents the energy required to move an internal electron from the Fermi Surface of a solid to its external surface, revealing the interactions between electrons and nuclei in the bulk solid. It has been found that the aforementioned properties are strongly dependent on the EWF raised to the sixth power [33][34][35][36], φ 6 . Similarly, Δρ [23,[37][38][39] captures the electron rearrangement and lattice distortion and, in turn, can be utilized to account for the enhanced hardness and understand how the solute atoms alter the bonding and strengthening character.…”
mentioning
confidence: 99%